The Worldwide Emergence of Liberal Education - Godwin, Kara A. (International Higher Education, 2015)
During the last two decades, liberal education (often called liberal arts or general education) has emerged with surprising prevalence in places where it has rarely existed before. A new study provides an inaugural profile about where, when, and in what format liberal education is emerging worldwide, identifies regional trends, and raises critical questions.